(untitled) (Medico Legal Update, 2021)
Background: Orbitofacial anthropometric measurements can be used in identification of gender and ethnicity in forensic anthropology. It also plays a crucial role used in plastic surgery and for identifying genetic syndromes. Canthus is the term employed to explain the either corner of the eyes. Inner canthus is also called as medial or nasal canthus. Outer canthus, is otherwise called as lateral or temporal canthus. Normal canthal values can function as a guide for the diagnosis of pathology and interventions for craniofacial abnormalities. Thus, it is necessary to have a knowledge about the local data of those parameters since this standard reflects the doubtless different pattern of craniofacial growth resulting from racial, ethnic, sexual and dietary differences. Hence this study is undertaken to find out the normative inner canthal and outercanthal distance measurement in population of South Indian region. Aims and Objectives: The present study was done to find out the normal inner and outercanthal distance and also canthal index of population of South Indian ethnic origin and also to analyse the sexual dimorphism in them. Materials and Method: This descriptive cross-sectional study was conducted on 200 volunteers of age group 18-25 years of both sexes belonging to South Indian region. Innercanthal distance(ICD) and Outer canthal distance(OCD) were measured using digital vernier caliper.Canthal index was calculated. All the data were analysed using SPSS 16.0 version software and correlated with gender. Results: Mean innercanthal distance was found to be 2.64 ±0.51 cm in males and 2.51 ±0.46 cm in females respectively in the present study. There is significant sexual dimorphism in ICD . The study also showed outercanthal distance to be 10.35± 0.81cm in males and 10.19 ±1.02 cm in females respectively. Canthal index was 25.71 ±4.91 in males and 24.83±7.83 in females. There is no significant sexual dimorphism in OCD and Canthal index. Conclusion: It was observed that all the values were significantly higher in males than females of south Indian ethnic origin. And there is a significant sexual dimorphism in inner intercanthal distance.